ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA PADA PELAKU PENANYANGAN PENJUALAN ORGAN GINJAL MANUSIA MELALUI INTERNET - Nella Elmata Lia; Hayatul Ismi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The internet is acomputer networkthroughout the world that is connected toeach other by using internet standards for human life. But the existence ofr theinternet is like a double-edged sword, besides contributing to improving humanwelfare, as well as being a mens of effective crime. Advertising activities usinginternet media through free buying and selling sites, are used by some people toadvertise items that are not legally for sale such as kidney organs. However, thearrangement has not been regulated, so the purpose of this thesis is; first, criminalresponsibility for the perpetrators of advertisements for selling human kidney organsthrough the internet, secondly, the imposition of sanctions on adversiting criminalsselling human kidney organs through the internet.This research is a type of normative research that examines law number 19 of2016 concerning information and electronic transactions, and other laws relating toproblems. This research is descriptive which is a research that aims to make apicture of the problem.The act of displaying kidney advertisements via the internet is a criminal act,because it has fulfilled the elements to be said to be a criminal act which includes 1.There are advertisers of perpetrators 2. Violating the values that live in society(against the material law) 3. No forgiveness and justification reasons. Although thereare no rules governing it formally, these acts can be classifried as criminal actsbecause they have violated the values that live in society, and encourage humantrafficking and violate health laws.The act of displaying advertisements for kidney organs through the internet isa criminal act and can be categorized as cyber crime, so it should be added to theITE law concerning criminal provisions against anyone who advertises goods thatare not it accordance with the legislation so that the perpetrators can be subject tosanctions